Facility management information taxonomy framework for queries in healthcare buildings - Demirdogen, G.; Isik, Z.; Arayici, Y. (ELSEVIER, 2021)
Healthcare facilities need to ensure providing safer services to patients without interruptions since disease diagnosis and treatments highly depend on medical equipment and spaces. Therefore, facility management (FM) of healthcare facilities requires a clear and rapid information flow for decision making processes to impede possible interruptions. Non-availability of information, accuracy problems and incomplete information induce more severe problems such as cost overruns, reduced productivity and decrease in customer satisfaction. Thus, this paper aims to develop a strategic information taxonomy framework for FM inquiries in healthcare facilities to address the research problem. Design Science Research methodology cycles such as relevance, rigor and design are adopted during the flow of the research. In the relevance cycle, research requirements and the importance of FMITs were firstly observed with two scenarios, then in the rigor cycle, 64 FM information types (FMITs) were determined, classified and refined under three categories such as; managerial, technical, and financial as a result of literature review and pilot study. Determined FMITs were analyzed with newly developed MonteCarlo Simulation and TOPSIS Techniques on healthcare facilities. As a result of analysis, 62 FMITs were found important for healthcare facilities. The most important FM Informations Types were found as identification of hazardous or other risks to people or property (0,985), real-time operation parameters/post occupancy data integration (0,939), and predicted lifetime of assets (0,818) in managerial, technical and financial information types respectively. Finally, in design cycle, facility management information taxonomy, which was created from determined FMITs, and importance levels of determined FMITs were evaluated with two case studies. Results showed that while maintenance contracts have a positive impact to prevent negative impact of costs, they can cause interruption in information management in facility management. Additionally, there are some view difference in professions. For example, construction management literature focuses wastes that are incurred at the end of building lifecycle or construction process. However, there aren't much attention to manage wastes that occurred during operation and maintenance stage. Beside this, regulations and standards have importance to store, use and manage FMITs. The analysis results acknowledged that the use of information taxonomy framework can increase the effectiveness of the healthcare FM.
Keywords: Facility management; Healthcare buildings; MonteCarlo and TOPSIS Techniques (MCTT); Information taxonomy; DESIGN SCIENCE RESEARCH; FAULT-DETECTION; BIG DATA; FUTURE; FM; CONSTRUCTION; SYSTEM; MODEL; REQUIREMENTS; ARCHITECTURE; Construction & Building Technology; Engineering